Uncovering the business opportunity prototype: Cognitive and learning aspects of entrepreneurial opportunity recognition in higher education - Costa, Sílvia Margarida dos Santos Fernandes (2015)
The research project underlying this thesis focuses on three main aspects of entrepreneurship. First, we focus on opportunity recognition as the point of departure for entrepreneurial thinking and entrepreneurial activity. Secondly, we propose that basic perceptive cognitive structures (such as prototypes) are fundamental to recognize opportunities at early stages of development of the entrepreneurial mindset. Third, we focus on cognitive and learning aspects of opportunity recognition with individuals in higher education. To explore these topics, the present thesis is divided in two parts. Part I focuses on the theoretical and empirical development of the topic on business opportunity prototype for opportunity recognition and includes three studies. Study 1 provides a systematic literature review of prototypes in entrepreneurship research. A theoretical model based on this analysis is presented and empirically tested on the remaining studies of the thesis. Study 2 explores the role of the context of business opportunity recognition on the identification of its prototypical features. Study 3 proposes a simplified business opportunity prototype to describe how individuals with no entrepreneurial experience perceive business opportunities from early stages of the entrepreneurial mindset. Part II focuses on the training and learning aspects of cognitive structures regarding opportunity recognition and includes one empirical study. Study 4 focuses on the effect of cognitive training and experiential learning on the development and accuracy of the business opportunity prototype. Moreover, the moderator role of positive affect towards entrepreneurship is tested in the learning process. This thesis aims to contribute to the enrichment of entrepreneurship as a field of research from a theoretical and conceptual, empirical, and practice perspectives.